Clinical Epidemiology of Pediatric COVID-19 Delta Variant Cases From North Sumatra, Indonesia - Kusumawati, R. Lia; Lubis, Inke Nadia Diniyanti; Kumaheri, Meutia Ayuputeri; Pradipta, Ariel; Faksri, Kiatichai; Mutiara, Mutiara; Shankar, Anuraj H.; Tania, Tryna (Frontiers in Pediatrics, 2022)
The Delta variant of SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) dominated the coronavirus disease 2019 (COVID-19) pandemic in 2021. Here we report the Delta variant among pediatric cases in North Sumatra, Indonesia, from June to July 2021. Whole-genome sequencing (WGS) from 18 new COVID-19 pediatric patients showed that six were B.1.459 and six were B.1.466.2, known variants in Indonesia in clade 20A. Six were the Delta variant B.1.617.2 of clade 21A, with five on one branch and one on a distant branch consistent with that patient's geographic separation, suggesting at least two introductions to the region. Variants tended to be spatially clustered, and four children with Delta variant had an adult infected household member, all of whom had lower real-time polymerase chain reaction cycle threshold (Ct) values compared with the child. No temporal trends were observed for Ct. These data support a paradigm shift with children being highly susceptible to the Delta variant and a priority for vaccination.